2000
DOI: 10.1074/jbc.275.3.2219
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Interactions Integrating Itk with the T Cell Receptor-initiated Signaling Cascade

Abstract: The T cell receptor (TCR), 1 B cell receptor, and mast cell receptor (Fc⑀RI) are composed of multiple subunits, enabling the coupling of a variable antigen-recognition subunit to conserved signaling modules (1-3). Collectively, these receptors direct the antigen-specific responses of T cells, B cells, and mast cells. Although these antigen receptors do not contain intrinsic tyrosine kinases, the early events downstream of these antigen receptors are controlled by a relatively conserved series of tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
245
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 260 publications
(256 citation statements)
references
References 86 publications
10
245
0
1
Order By: Relevance
“…A fusion protein encompassing the proline-rich region of Emt/Itk, but excluding the SH3 and SH2 domains, was able to interact with LAT, but not with SLP-76. Because LAT does not contain a complementary SH3 domain to bind to the proline-rich region of Emt/Itk, we suggest that this interaction is due to an intermediate protein such as Grb2, which contains both SH3 and SH2 domains, with the latter known to interact with LAT (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A fusion protein encompassing the proline-rich region of Emt/Itk, but excluding the SH3 and SH2 domains, was able to interact with LAT, but not with SLP-76. Because LAT does not contain a complementary SH3 domain to bind to the proline-rich region of Emt/Itk, we suggest that this interaction is due to an intermediate protein such as Grb2, which contains both SH3 and SH2 domains, with the latter known to interact with LAT (28).…”
Section: Discussionmentioning
confidence: 99%
“…SLP-76 is an important adapter protein that is phosphorylated by ZAP-70 and is required for PLC␥1 activation, intracellular Ca 2ϩ mobilization, IL-2 production, and development of T lymphocytes (29 -33). Bunnell et al (28) showed that GST-SH2 fusion proteins interacted only with phosphorylated SLP-76, whereas GST-SH3 constructs reacted with SLP-76 regardless of its phosphorylation status. Because of the inability of full-length Emt/Itk to interact with unphosphorylated SLP-76, these authors suggested that the SH3 domain is sequestered in the intact Emt/Itk molecule and, furthermore, that the finding that SLP-76 possesses adjacent binding sites for the Emt/Itk SH2 and SH3 domains suggested that the interaction of SLP-76 with Emt/ Itk may represent a synergistic effect between these two domains (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N terminus harbors three tyrosines that become phos- phorylated upon TCR engagement [5,6] and have been reported to serve as docking sites for the guanine nucleotide exchange factor Vav, the adaptor protein Nck, the Tec family kinase Itk, and the p85 subunit of PI3K [7][8][9][10][11][12][13][14][15][16]. A single SH2 domain resides in the C-terminal portion of SLP-76 and links it to the adhesion and degranulation-promoting adaptor protein (ADAP) and to the hematopoietic progenitor kinase 1 [17][18][19].…”
Section: Introductionmentioning
confidence: 99%